IMPLEMENTASI FIREWALL FILTERING PADA SITUS WEB DAN GAME ONLINE MENGGUNAKAN LAYER 7 PROTOCOLS DAN MANAJEMEN BANDWIDTH DENGAN METODE HIERARCHICAL TOKEN BUCKET - Muhlis Tahir; Abdullah Bachtiar Rifai (LPPM Universitas Dhyana Pura, 2026)
The development of computer network technology has a significant impact in supporting the learning process. However, without good network management, the use of the internet can cause problems such as accessing irrelevant sites and uneven bandwidth distribution. This research aims to implement firewall filtering using Layer 7 protocols and bandwidth management using the Hierarchical token bucket (HTB) method on Mikrotik devices in the computer laboratory of SMK Negeri 3 Bangkalan. This research is included in the type of development research using the NDLC (Network Development Life Cycle) network development model. The implementation results show that the firewall successfully blocks access to inappropriate websites and online games. Based on the Quality of service (Qos) test results, there was an increase in throughput from 189 bps to 2534 bps, packet loss was successfully maintained at 0%, delay from 49.85 ms to 3.94 ms, and jitter from 47.8 ms to 6.75 ms. These results show that the implementation of HTB has a significant impact on improving network efficiency and stability.